2018
DOI: 10.3389/fpsyt.2018.00479
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Emotion in Functional Neurological Disorder

Abstract: Emotions have traditionally been considered crucial in the development of functional neurological disorder, but the evidence underpinning this association is not clear. We aimed to summarize evidence for association between functional neurological disorder and emotions as formulated by Breuer and Freud in their conception of hysterical conversion. Based on a systematic literature search, we identified 34 controlled studies and categorized them into four groups: (i) autonomic arousal, (ii) emotion-motion intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 123 publications
0
18
0
1
Order By: Relevance
“…A growing body of neuroimaging evidence supports the notion that abnormal emotional processing is a key factor in the etiology of functional neurological symptoms (1, 2). Task-based neuroimaging studies show limbic and paralimbic hyperactivation (35), abnormal limbic-motor circuit connectivity (46), and altered activation of several prefrontal regions in emotion processing tasks in various groups of patients with FND (3, 69).…”
Section: Introductionmentioning
confidence: 92%
“…A growing body of neuroimaging evidence supports the notion that abnormal emotional processing is a key factor in the etiology of functional neurological symptoms (1, 2). Task-based neuroimaging studies show limbic and paralimbic hyperactivation (35), abnormal limbic-motor circuit connectivity (46), and altered activation of several prefrontal regions in emotion processing tasks in various groups of patients with FND (3, 69).…”
Section: Introductionmentioning
confidence: 92%
“…Antidepressants may have multiple actions, including possible central analgesic effects (Lynch, 2001), and reductions in affective arousal and sleep dysfunction (Clouse et al, 1994). The relationship between antidepressant treatment and mFND prognosis remains complicated by the presence of co-morbid depression and anxiety, as well as other factors such as attachment traits (Jalilianhasanpour et al, 2018), emotional regulation (Sojka et al, 2018), attentional dysregulation (Edwards et al, 2012), health anxiety and illness belief (Bakvis et al, 2009), and phobic avoidance (Stone et al, 2012). As it stands, the effectiveness or otherwise of antidepressants in this group and their mechanism of action remain poorly understood.…”
Section: Accepted Manuscript 20mentioning
confidence: 99%
“…Our understanding of FND has made considerable advances, with implications for diagnosis and treatment. Research into the pathophysiology of FND has challenged old assumptions about the disease as a primarily psychological illness ( 5 ). It has been widely demonstrated that symptoms are more consistently explained by abnormalities in high-order cognitive functions involving attention and sense of agency (e.g., feeling of control over abnormal bodily movement) rather than by psychological difficulties ( 6 ).…”
Section: Introductionmentioning
confidence: 99%